Lake bacterioplankton dynamics over diurnal timescales. (January 2017) - Grubisic, Lorena M.; Bertilsson, Stefan; Eiler, Alexander; Heinrich, Friederike; Brutemark, Andreas; Alonso‐Sáez, Laura; Andersson, Anders F.; Gantner, Stephan; Riemann, Lasse; Beier, Sara
Summary: Planktonic bacterial community dynamics over short timescales can be of great importance for food webs and ecosystem functioning but are rarely described when microbial community and composition are assessed. To study the significance of such dynamics we sampled the surface water at the deepest point of a mesotrophic lake (Lake Erken, Sweden) every third hour over two days. By combining 454 pyrosequencing of 16S rRNA genes with bromodeoxyuridine immunocapturing of DNA, replicating populations were identified and compared to the community retrieved from total DNA samples. This comparison revealed a significant difference between the actively replicating and total community. The high‐frequency diurnal sampling was compared to a year‐long survey conducted in the same lake in order to compare the diurnal and seasonal variation in bacterioplankton community composition. At the diurnal‐scale, the variation was significantly higher in the replicating than in the total community. However, variation in both active and total diurnal community was significantly lower than the variation in the seasonal total community. Our analysis revealed pronounced short‐term dynamics of individual bacterial populations uncoupled from the diurnal light cycle. For example, the proliferating fraction of the most abundant bacterial tribe (LD12) followed a cyclic pattern that covaried with viral abundance. This implies that environmental factors other than light may act as important drivers of microbial community composition, at least in mesotrophic Lake Erken.